Development of constant cutting input force scissors for force sensing (Confirmation of basic principle) - Satsuya NODA; Koki YOSHIDA; Motomu YOSHIDA; Masaki WARAGAI (Nihon Kikai Gakkai ronbunshu, 2022)
To improve robot manipulability, force sensing for scissors is expected to be significant. In general scissors, the moment and the crossing angle of the blade depends on the cutting position, resulting in the difference of the required input force for cutting. Though logarithmic spiral scissors enables to equalize crossing angle of scissors blade, the scissors also causes the moment difference. This paper proposes a mechanical motion conversion mechanism which equalizes the cutting input force of logarithmic spiral scissors. For the mechanical motion conversion mechanism, we suggest a curved slider mechanism which is combined with a linear slider. Because the curved shape can be calculated by analytic method, the linear slider stroke design procedure is simple compared with 4 linkage mechanism. Furthermore, the proposed mechanism enables to control the cutting speed easily compared with the former studies because the cutting speed is proportional to the linear slider speed. In the geometric and mechanical experiments using dummy scissors(40 mm in blade length), we confirmed that the cutting input force was independent of the cutting position if the constant load is applied. In the kent paper experiments using usual logarithmic spiral scissors (65 mm in blade length), the proposed mechanism could convert the constant load excepting friction effect.